2012
DOI: 10.1097/nen.0b013e3182625c02
|View full text |Cite
|
Sign up to set email alerts
|

Cell of Origin Determines Tumor Phenotype in an Oncogenic Ras/p53 Knockout Transgenic Model of High-Grade Glioma

Abstract: Human high-grade gliomas (HGGs) are known for their histologic diversity. To address the role of cell of origin in glioma phenotype, transgenic mice were generated in which oncogenic Ras and p53 deletion were targeted to neural stem/progenitor cells (NSPCs) as well as mature astrocytes. hGFAP-Cre/KrasG12D/p53fl/fl mice develop multifocal HGG that vary histopathologically and with respect to the expression of markers associated with NSPCs. One HGG pattern strongly expressed markers of NSPCs and arose near the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Under the stem cell hypothesis, Olig2 fulfills criteria of a lineagerestricted compe tence factor for gliogenesis [8,15] that is necessary for the development of neural progenitors and prog eny cells in the CNS [12]. Like others, [22] we have suggested that Olig2 expression may be downregu lated in mature astrocyte.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Under the stem cell hypothesis, Olig2 fulfills criteria of a lineagerestricted compe tence factor for gliogenesis [8,15] that is necessary for the development of neural progenitors and prog eny cells in the CNS [12]. Like others, [22] we have suggested that Olig2 expression may be downregu lated in mature astrocyte.…”
Section: Discussionmentioning
confidence: 96%
“…Subventricular zone may be a source of tumors with higher proliferative and invasive capaci ties [5]. Recent research efforts in neurooncology are focused in targeting the tumorigenesis theory and to find signal transduction pathways that influence the GB development and change its dismal progno sis, given that surgery and adjuvant chemotherapy with radiotherapy are insufficient due to a diffuse infiltration by tumor tissue into the brain [4,12,37]. Therefore, identifying molecular targets that could provide prognostic new data is needed and would be helpful for its therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations